Clinical characteristics and prognostic analysis of multiple primary malignant neoplasms in female patients with breast cancer or genitalia malignancies - Xiao, Li; Cao, Tiantian; Ou, Jiali; Liang, Weijiang (PeerJ, 2022)
Background As public awareness of health has increased and diagnostic and treatment options have improved, the survival of patients with malignant tumors has continued to extend, and the population has been aging, the number of multiple primary malignant neoplasms has gradually increased in recent years. There are few reports concerning female patients with multiple primary malignant neoplasms of breast cancer or genitalia malignancies. In this study, we aimed to analyze the clinical characteristics and prognosis of multiple primary malignant neoplasms in female patients with breast cancer or genitalia malignancies, as well as further explore the factors that affect the survival. Methods We collected clinical data on 80 female patients diagnosed with multiple primary malignant neoplasms of the breast or genitalia, described their clinical features. Furthermore, we calculated the survival and prognostic factors for 52 participants. Results In our study, the prevalence rate of multiple primary malignant neoplasms was 0.66% (367/55404). Corresponding to female patients with multiple primary malignant neoplasms of breast cancer or genitalia malignancies, it was 1.4% (80/5707). the median age of diagnosis for the first tumor was 48 years, and the median age of diagnosis for the second tumor was 52 years. Regarding the interval, 67.57% (50/74) of patients were within five years. Most tumors were located in the breast (44.68%), followed by the uterus (20.21%), the ovary (17.02%), and the cervix (15.96%). The overall 12-, 36-and 60-month survival rates of the patients were 86.4%, 74.3%, and 69.8%. For the female patients, the stage (III–IV) (P = 0.046), non-radical surgery (P = 0.002), and types of the last tumor (breast cancer or genitalia malignancies) (P = 0.019) were associated with the poor prognosis. Conclusions Female patients with breast cancer or genital malignancies should pay attention to screening for the second tumor, especially within 4 years after the first tumor diagnosed. Furthermore, during tumor screening, it may be recommended for these patients to focus on colorectal cancer and lung cancer. Compared with previous studies, in addition to clinical staging and types of surgery, we found whether the last tumor was breast cancer or genitalia malignancies should also be considered a prognostic factor.
Keywords: Multiple primary malignant neoplasms; Female; Breast cancer; Genitalia malignancies